Membangun Nasionalisme Generasi Z melalui Dialog Intergenerasi dan Media Digital Berbasis Nilai Lokal di Desa Bioa Sengok - Muhammad Fauzan Aziman; Yogopriyatno, Jatmiko; Susanti, Is; Fariz Antonius Azhari (Yayasan Literasi Sains Indonesia, 2025)
This community service program aims to develop a model for strengthening Generation Z nationalism through integration of intergenerational dialogue with digital media based on local values in Bioa Sengok Village, Lebong Regency, Bengkulu. This village is a remote rural area in Sumatran highlands with mountainous topography and limited infrastructure access. Partner problems include low understanding of national values among Gen-Z, lack of intergenerational dialogue spaces, and suboptimal use of digital media in the context of digital divide due to mountainous topography. Participatory action research methods were applied involving 25 Gen-Z participants through interactive dialogue series, digital content production workshops, and development of